A High Spatial and Spectral Resolution Study of Jupiter’s Mid-infrared Auroral Emissions and Their Response to a Solar Wind Compression - James A. Sinclair; Thomas K. Greathouse; Rohini S. Giles; John Lacy; Julianne Moses; Vincent Hue; Denis Grodent; Bertrand Bonfond; Chihiro Tao; Thibault Cavalié; Emma K. Dahl; Glenn S. Orton; et al. (The Planetary Science Journal, 2023)
We present mid-infrared spectroscopy of Jupiter's mid-to-high latitudes using the Gemini-North/Texas Echelon Cross Echelle Spectrograph on 2017 March 17–19. These observations capture Jupiter’s hydrocarbon auroral emissions before, during, and after the arrival of a solar wind compression on March 18, which highlights the coupling between the polar stratosphere and external space environment. In comparing observations on March 17 and 19, we observe a brightening of the CH _4 , C _2 H _2 , and C _2 H _4 emission in regions spatially coincident with the northern duskside main auroral emission (MAE). In inverting the spectra to derive atmospheric information, we determine that the duskside brightening results from upper stratospheric ( p < 0.1 mbar/ z > 200 km) heating (e.g., Δ T = 9.1 ± 2.1 K at 9 μ bar at 67.°5N, 162.°5W) with negligible heating at deeper pressures. Our interpretation is that the arrival of the solar wind enhancement drove magnetospheric dynamics through compression and/or viscous interactions on the flank. These dynamics accelerated currents and/or generated higher Poynting fluxes, which ultimately warmed the atmosphere through Joule heating and ion-neutral collisions. Poleward of the southern MAE, temperature retrievals demonstrate that auroral-related heating penetrates as deep as the 10 mbar level, in contrast to poleward of the northern MAE, where heating is only observed as deep as ∼3 mbar. We suggest that this results from the south having higher Pedersen conductivities and therefore stronger currents and acceleration of the neutrals, as well as the poleward heating overlapping with the apex of Jupiter's circulation, thereby inhibiting efficient horizontal mixing/advection.